The evil within - MacPhail, Catherine (Edinburgh: Barrington Stoke, 2017)
Scotland, 1850. Night after night, the closes and alleys of Edinburgh's Old Town are alive with horror. Who or what is the beast haunting the dark city? A few streets away, in his respectable New Town home, young Harry Jekyll wakes from yet another nightmare. His hands are covered in blood ... What evil lurks within young Jekyll?
Keywords: Horror tales